Age and Comorbidities as The Main Factors of Mortality in Covid-19 Patients : A Retrospective Cohort Study - Mas’udah, Anni Fithriyatul; Purwanti, Lina Ema; Ernawati, Hery; Rohma, Naylil Mawadda; Muslimah, Vanesha Awaliya; Muslimah, Vanesya Isnaya (IJNP (Indonesian Journal of Nursing Practices), 2023)
Background: The high mortality rate in COVID-19 patients is associated with demographic factors and comorbid conditions. This is supported by research which shows that a history of comorbidities causes 88% of deaths in SARS-CoV-2 positive patients.Consequently, it is important to identify factors associated with poor outcomes among COVID-19 patients.Objective: The purpose of this study was to determine the main factors that cause COVID-19 mortality in Indonesia.Methods: The research design used a retrospective cohort. The population of this study was all Covid-19 patients treated at the 'Aisiyah Ponorogo General Hospital from March to December 2021, totalling 881. The data was arrangedbased on the completeness of the medical records, and seven respondents had to be excluded due to incomplete data. Therefore, the total number of samples used was 874 patients. Data was analyzed using logistic regression.Result: The multivariate analysis showed that patients aged 46-65 years were 1.45 times greater potential to die than than patients who were 0-25 years old.  The risk factors for comorbidities had an effect on the mortality of patients with confirmed cases of COVID-19.The variables that had a significant effect on the mortality of COVID-19 included Diabetes mellitus (OR=1.36), Hypertension (OR = 1.78) and heart disease (OR = 1.4).Conclusion: The most common causes of mortality in Covid-19 patients are age and comorbidities diseases, there are diabetes mellitus, hypertension and heart disease